PROSPEK STUDI HADIS DI INDONESIA (Telaah atas Kajian Hadis di UIN, IAIN, dan STAIN) - Suryadi, Suryadi (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2015)
Ministry of Religious issued the new nomenclature of the separation of the field of study of the Qur’an and the Hadith, which was a single entity by the name of Tafsir Hadith (TH). This paper is to research on the current prospect of Hadith studies in UIN, IAIN and STAIN after the new nomenclature was brought. It comes to a conclusion that after the new nomenclature, Hadith studies in Indonesia has a little prospect to develop in the future. Solutions offered by this paper is to reintegrate the Qur’an studies and Hadith studies into Tafsir Hadith studies and to separate the two fields only at the graduate level, and create a consortium of the science of Hadith.